Phylogeny and Historical-Geographical Analysis of Yersinia pestis Strains from Vietnam - K. A. Nikiforov; L. M. Kukleva; Zh. V. Al’khova; E. G. Oglodin; M. A. Makashova; E. A. Naryshkina; N. P. Guseva; G. A. Eroshenko; Hong Chien Dang; Mo Thi Lyong; Viet Kyong Vo; V. V. Kutyrev (Проблемы особо опасных инфекций, 2020)
Objective of the work was to identify molecular-genetic peculiarities, to conduct whole genome sequencing and phylogenetic analysis of Yersinia pestis strains isolated inVietnam between 1962 and 1989.Materials and methods. We have studied the properties of 50 Y. pestis strains, carried out whole genome sequencing of 18 and fragment sequencing of 32 strains from Vietnam. Phylogenetic analysis was performed on the basis of whole genome SNPanalysis by 1391 identified SNPs. Whole genome SNP-analysis and search for marker SNPs were conducted applying Wombac 2.0 software package. Phylogenetic diagram construction was done using Maximum Likelihood algorithm.Results and discussion. Several phylogenetic branches and Y. pestis populations coinciding with geographical and historical dissemination of the strains have been distinguished. The major part of the strains from Vietnam falls under the branch designated by us as 1.ORI2v. Two strains form a separate branch together with the strain from India belonging to 1.ORI2 line, one more strain, 55-801 Saigon, is set among the strains of 1.ORI1 line. Based on the data obtained and evidence from the literature sources it can be assumed that introduction of plague into Vietnam occurred through several waves: Nha Trang city in 1898, by sea; north provinces of the country – 1908. The second wave of Y. pestis dissemination across the territory of Vietnam began in 1960s with the emergence of the strains from the natural plague focus in Yunnan province, China.